Gut-Homing Conventional Plasmablasts and CD27− Plasmablasts Elicited after a Short Time of Exposure to an Oral Live-Attenuated Shigella Vaccine Candidate in Humans - Toapanta, Franklin R.; Simon, Jakub K.; Barry, Eileen M.; Pasetti, Marcela F.; Levine, Myron M.; Kotloff, Karen L.; Sztein, Marcelo B. (Frontiers in Immunology, 2014)
Currently, there is no licensed Shigella vaccine; however, various promising live attenuated vaccine candidates have emerged, including CVD1208S (ΔguaBA, Δset, Δsen S. flexneri 2a), which was shown to be safe and immunogenic in Phase 1 clinical trials. Here we report the immune responses elicited in an outpatient Phase 2 clinical trial in which subjects were vaccinated with CVD 1208S. Oral immunization with CVD 1208S elicited high anti-S. flexneri 2a LPS and IpaB antibody responses, as well as an acute plasmablast (PB) infiltration in peripheral blood 7 days after immunization. PB sorted based on their expression of homing molecules confirmed that cells expressing integrin α4β7 alone or in combination with CD62L were responsible for antibody production (as measured by ELISpot). Furthermore, using high-color flow-cytometry, on day 7 after immunization, we observed the appearance of conventional PB (CPB, CD19dim CD20- CD27+high CD38+high CD3-), as well as a PB population that did not express CD27 (CD27- PB; pre-plasmablasts). The pattern of individual or simultaneous expression of homing markers (integrin α4β7, CD62L, CXCR3 and CXCR4) suggested that CPB cells homed preferentially to the inflamed gut mucosa. In contrast, 50% CD27- PB cells appear to home to yet to be identified peripheral lymphoid organs or were in a transition state preceding integrin α4β7 upregulation. In sum, these observations demonstrate that strong immune responses, including distinct PB subsets with the potential to home to the gut and other secondary lymphoid organs, can be elicited after a short time of exposure to a shigella oral